179:oral Priority-setting for effective pandemic preparedness: a case study of priority setting for COVID-19 in the Western Pacific Region. (28th April 2022) - Essue, Beverley M; Valez, Claudia Marcella; Goold, Susan; Nouvet, Elyse; Kapiriri, Lydia; ,
Abstract : Background: There have been divergent approaches used by countries to curb and control the spread, impact and burden of COVID-19. While priority setting – defined as decision-making about the allocation of resources between competing claims of different services, populations and elements of care – is recognized as critical for promoting accountability and transparency in health system planning, its role in supporting rational, equitable and fair pandemic preparedness planning is less well understood. Our multi-country project investigates the effectiveness of priority setting for pandemic preparedness planning. This study aims to describe how priority setting guided the COVID-19 responses implemented in the sub-set of countries in the Western Pacific Region. Methods: Guided by the adapted Kapiriri and Martin Framework, we purposively sampled a subset of countries in the WHO Western Pacific Region (WPRO) and undertook a critical document review of national-level pandemic preparedness plans. A pre-specified, validated tool guided data extraction on twenty quality parameters of PS. A critical synthesis was completed. Results: Nine plans were included (41% WPRO countries), including: Papua New Guinea, Tonga, Philippines, Fiji, China, Australia, New Zealand, Japan, and Taiwan. There was evidence of strong political will to quickly and effectively combat the pandemic. With 8/9 countries being islands, an emphasis on securing boarders was reflected in the plans. A limited number of quality indicators of effective priority setting were described. Most commonly, plans described resource needs (n=8), stakeholder engagement (n=8), and responsibilities of legitimate institutions (n=7). Consideration of health inequalities, fair financial burden, or public engagement/acceptance of priorities was not evident in any plans. Discussion: This project advances understanding of how priority setting has been used in the WPRO region to support COVID-19 responses. It provides a basis for examining the relationship between effective priority setting for pandemic preparedness and country-level outcomes in future work.